Fostering Success and Motivating EFL Learners Using Zoom Meeting: A Synchronous Learning Strategy - Muhammad Nuryanto (Anglophile Journal, 2021)
Due to the rapid advancement of technology, teachers were forced to integrate technological equipment and method in educational strategies, for the main purpose of facilitating the learning experience. Accordingly, this study aimed to answer two main questions namely; 1) How can Zoom Meeting enhance high school students at Salatiga to gain success in ELT? 2) To what extent does use the Zoom Meeting as an asynchronous learning strategy affect the motivation of high school students at Salatiga? For that purpose, the researcher implemented an experimental design with a mixed approach to conduct the current study using a pre-test, and a post-test to measure the change in the levels of EFL learners’ English skills, the researcher also spread questionnaires to examine the attitude of the students towards the Zoom meeting. The participants of the current study were 60 high school students at Salatiga who were divided into two groups namely the control and experimental group. The findings indicated that zoom meeting enhanced EFL learners’ English skills and motivation Keywords: Zoom Meeting, Synchronous Learning Strategy, Zoom Meeting Learning